2020
DOI: 10.1038/s41598-020-58425-5
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of papillary thyroid cancer and its association with extra-thyroidal invasion

Abstract: Nerves are emerging regulators of cancer progression and in several malignancies innervation of the tumour microenvironment is associated with tumour aggressiveness. However, the innervation of thyroid cancer is unclear. Here, we investigated the presence of nerves in thyroid cancers and the potential associations with clinicopathological parameters. Nerves were detected by immunohistochemistry using the pan-neuronal marker PGP9.5 in whole-slide sections of papillary thyroid cancer (ptc) (n = 75), compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 35 publications
(49 reference statements)
0
40
0
Order By: Relevance
“…207 This suggests that during cancer, the molecules that promote angiogenesis could also induce axonogenesis/ neurogenesis mechanisms and vice versa. In fact, tumors are innervated mainly by sympathetic fibers, 208 this correlates with the high parallelism of sympathetic nerves and body vasculature.…”
Section: Sema4f Knock Downmentioning
confidence: 99%
See 1 more Smart Citation
“…207 This suggests that during cancer, the molecules that promote angiogenesis could also induce axonogenesis/ neurogenesis mechanisms and vice versa. In fact, tumors are innervated mainly by sympathetic fibers, 208 this correlates with the high parallelism of sympathetic nerves and body vasculature.…”
Section: Sema4f Knock Downmentioning
confidence: 99%
“…219 Tumors are innervated by sensorial fibers, in papillary thyroid cancer are detected peptidergic (sensorial fibers) and cholinergic (parasympathetic fibers) innervations, although most nerves are commonly adrenergic (sympathetic fibers). 208 Direct communication between sensorial afferent fibers and cancer cells stimulates proliferation and invasion of transformed cells. In breast cancer cells, NK1 receptors, stimulated by SP, activate secretory pathways that increase extracellular activity of metalloproteinases (MMPs); turning on HER2 growth factor receptor transactivation which, via Src, elicits proliferative and invasive processes.…”
Section: Sema4f Knock Downmentioning
confidence: 99%
“…It has been suggested that the innervation of cancer tissue is a new hallmark of cancer [ 114 ]. In support of this, it has been demonstrated that increased nerve size and density represents a negative prognostic marker of cancer disease [ 7 , 115 , 116 , 117 , 118 ].…”
Section: Drugs Reducing Density or Activity Of Nerves Innervating Cancer Tissuementioning
confidence: 90%
“…Neurotransmitters released from nerves innervating cancer exert complex effects on cancer progression and the development of metastases [ 122 ]. These effects depend on the type of nerves [ 105 ] and their density in cancer tissue [ 7 , 115 , 116 , 117 , 118 ]. For example, norepinephrine released from sympathetic nerves plays an important role in the initial phases of prostate cancer development, while acetylcholine released from parasympathetic nerves potentiates the progression of prostate cancer and development of metastases [ 7 ].…”
Section: Drugs Reducing Density or Activity Of Nerves Innervating Cancer Tissuementioning
confidence: 99%
“…Rowe et al 49 investigated the clinical relevance of nerves in thyroid cancer. A meticulous assessment of nerve density was performed in papillary and follicular thyroid cancers, and in normal thyroid tissue from unrelated patients.…”
Section: Accepted Articlementioning
confidence: 99%